2016
DOI: 10.1038/srep32793
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia deposition in the neighbourhood of an intensive cattle feedlot in Victoria, Australia

Abstract: Intensive cattle feedlots are large emission sources of ammonia (NH3), but NH3 deposition to the landscape downwind of feedlots is not well understood. We conducted the first study in Australia to measure NH3 dry deposition within 1 km of a commercial beef cattle feedlot in Victoria. NH3 concentrations and deposition fluxes decreased exponentially with distance away from the feedlot. The mean NH3 concentrations decreased from 419 μg N m−3 at 50 m to 36 μg N m−3 at 1 km, while the mean NH3 dry deposition fluxes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…There is a generally 5-10% increase over the eastern United States. This is consistent with an observed large increase of the NH x depositions and decrease of NO y depositions in northeastern United States from 1990s to 2010s (Du et al, 2014;Li et al, 2016). A possible explanation is that the implementation of emission control stretegies such as the Clean Air Act (CAA) has resulted in a large reduction in 530 NO x emssions, which lowered the NO y deposition in the United States (Lloret and Valiela, 2016).…”
supporting
confidence: 67%
See 2 more Smart Citations
“…There is a generally 5-10% increase over the eastern United States. This is consistent with an observed large increase of the NH x depositions and decrease of NO y depositions in northeastern United States from 1990s to 2010s (Du et al, 2014;Li et al, 2016). A possible explanation is that the implementation of emission control stretegies such as the Clean Air Act (CAA) has resulted in a large reduction in 530 NO x emssions, which lowered the NO y deposition in the United States (Lloret and Valiela, 2016).…”
supporting
confidence: 67%
“…6(e)). Also, the Asian regions have several high where it is emitted (Shen et al, 2016), while NO x can be oxidized to organic nitrate (Moxim et al, 1996), which facilitates the long-range transport from land to open ocean.…”
Section: Nh X Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MMM overestimates the SO 2 , SO 2− 4 , HNO 3 , NO − 3 and NH + 4 concentrations by 394, 40, 217, 135 and 173 %, respectively. It should be noted that the CASTNET sites are generally located in rural regions that are away from emission sources (Sickles and Shadwick, 2008); thus the measured concentrations of air pollutants are relatively low compared with those of urban sites, while the resolutions of the HTAP II models range from 0.5 to 3 • and are not fine enough to reproduce the characteristic of some rural sites. The models with finer resolutions except CHASER_t106 model (i.e., EMEP_rv48 (0.5 • × 0.5 • ) and SPRINTARS (1.1 • × 1.1 • )) generally perform better than the others, while models with coarse resolutions (i.e., CHASER_re1 (2.8 • × 2.8 • ) and OsloCTM3.v2 (2.8 • × 2.8 • )) generally do not perform well for all species.…”
Section: Dry Depositionmentioning
confidence: 99%
“…Ammonia is mainly emitted from the ground or near the vents of animal farms, and thus may have a higher deposition rate around the emission sources. Studies on NH 3 deposition around animal farms in Europe, America, and Australia have shown that there were high NH 3 deposition rates around the sources of NH 3 emissions (Fowler et al 1998;Walker et al 2008;Shen et al 2016). Measures such as planting trees around the sources were proposed to increase the near-source deposition of NH 3 , and to reduce the long-distance transportation of NH 3 , so as to reduce its environmental hazards (Bealey et al 2016).…”
Section: Introductionmentioning
confidence: 99%